Land Dispute Arrangements in Indonesia - Yustini, Ledy Wila (Universitas Muhammadiyah Palembang, 2023)
Land conflict is a process of interaction between two (or more) or groups each fighting for their interests over the same object, namely land and other objects related to land, water, plants, mines, as well as the air that is above the land. concerned. Various land disputes in Indonesia need to be examined why these disputes have not been resolved and have even been protracted and widespread in all corners of the land in Indonesia. It is necessary to find the root causes of the disputes that have occurred in Indonesia, so that it is necessary to discuss what is the cause of land disputes in Indonesia. This research method uses normative juridical research methods, carried out based on the main legal materials by examining theories, concepts, legal principles, online news references and laws and regulations related to land regulations. The conclusions obtained that the causes of land disputes in Indonesia are: 1.dualism of agrarian law, 2.differences in interpretation of an object, namely cooperation agreements regarding the management of land rights, 3.land mafia, 4.inaccurate and incomplete land data plus Incorrect land data, 5.Actions of applicants for land rights with a background of group interests or political indications, 6.Unbalanced land tenure and ownership structures, 7.Law enforcers do not yet have the commitment to consistently and consistently implement laws and regulations.